2019
DOI: 10.21660/2019.62.94618
|View full text |Cite
|
Sign up to set email alerts
|

Car Ownership Demand Modeling Using Machine Learning: Decision Trees and Neural Networks

Abstract: A household car ownership modeling is crucial in understanding the impact on an individual's or a family's travel behavior in traveling demand analysis. Trips or tours as a unit of analysis can be used in the modeling of car ownership demand for analyzing travel needs. Machine learning is widely used to describe a car owner's decision since the machine learning model was specifically designed to give more accurate predictions through a variety of mechanisms. This research presents car ownership modeling using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The findings in this study throws more light on vehicle ownership in the context of a small to medium urban city in Ghana which is mainly influence by the respondents travel characteristics and average monthly income. This finding is largely in agreements with the studies by Ha et al [ 33 ], Kaewwichiann et al [ 34 ] and Paredes et al [ 32 ], however, with regards to the best performing ML algorithm, the finding in our study produced different results which might be as a result of the difference in the data structure and the methods used to find the best learning features for each algorithm, highlighting the case-specific nature of the application of the ML algorithms to vehicle ownership studies.…”
Section: 0 Conclusionsupporting
confidence: 94%
See 2 more Smart Citations
“…The findings in this study throws more light on vehicle ownership in the context of a small to medium urban city in Ghana which is mainly influence by the respondents travel characteristics and average monthly income. This finding is largely in agreements with the studies by Ha et al [ 33 ], Kaewwichiann et al [ 34 ] and Paredes et al [ 32 ], however, with regards to the best performing ML algorithm, the finding in our study produced different results which might be as a result of the difference in the data structure and the methods used to find the best learning features for each algorithm, highlighting the case-specific nature of the application of the ML algorithms to vehicle ownership studies.…”
Section: 0 Conclusionsupporting
confidence: 94%
“…In other words, it is the measure of how scores of an estimator reduce when a feature is excluded from the model estimation. A reduction in the model scores indicates how important this feature is, in the overall performance of the model (see [ 23 , 34 , 48 ] for more details).…”
Section: 0 Dataset and Modeling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In [35], the authors propose an ensemble method-ensembling the results of separate NN regressors-to predict household electricity consumption based on a set of household characteristics including the number of rooms, the total floor space and the number of residents. In [36], car ownership in Thailand is predicted from independent variables relating to household socio-economic factors, activities and accessibility using both NNs and decision trees. By defining the problem as a classification, in which the number of cars per household is classified as either 0, 1 or 2+, it is shown that neural networks statistically outperform decision trees.…”
Section: Previous Work On Car Ownership Modellingmentioning
confidence: 99%
“…This method predicts different data types, either present or future, such as travel demand predictions. Several minor models were used, including the household car ownership models, trip generation models, tour generation models, trip distribution models, travel time choice models, and travel route choice models [1], with either trip or tour used as the unit of analysis [2]. There are several techniques for data classification [3], e.g.…”
Section: Introductionmentioning
confidence: 99%